Quality of Life Related to Health on Patients Suffering from Cerebrovascular Diseases at 2 Years of Survival - Rubén Bembibre Taboada; Diosdania Alfonso Falcón; Carlos Jaime Geroy Gómez; Miguel Angel Buergo Zuaznábar; Inti Santana Carballosa (Medisur)
Background: Quality of life related to health is a reliable and necessary indicator for the analysis of the sanitary state in a community. It is also a data source to define strategies in health actions in a population. Objective: To describe the aspects related to quality of life in two- year survivors from cerebrovascular disease. Method: A retrospective and prospective, descriptive study of a serie of cases with quality of life assessment related to patient’s health two years after being discharged from hospital due to ictus. A simple random sampling was performed and applied to survivors. Quality of life scale for ECVI–38 ictus was used determining the most affected cerebral dominance by means of statistic techniques. Results: the quality of life assessment in ictus showed a general mean of 46.5. The spheres identified as more engaged were the feelings and the emotional one. Illness in several of the cerebral dominance was confirmed in the majority of survivors although the obtained measurements were not high. The level of recovering at two years of the beginning of the disease was little or none in 31 ill patients. Conclusions: Alterations in quality of life related to health are sequelae which in more or lesser degree suffer from the majority of the survivors to a neuroictus. These can be determined applying ECVI-38. It is necessary to take measures to minimize the deleterious effects and fulfill the objectives for survivors have a satisfactory quality of life.